Education As Ethical-affective Resistance: Pedagogical Bridges Between Southern Europe And The Maghreb - Baptista , Nuno (Social Empowerment Journal, 2025)
This theoretical essay explores the concept of ethical-affective resistance in education, examining pedagogical bridges between Southern Europe and the Maghreb. Drawing on critical and decolonial perspectives—especially the work of Freire, hooks, Zembylas, and Santos - it conceptualises education as a relational, political, and affective practice capable of challenging hegemonic structures and revaluing marginalised knowledges. The essay addresses the enduring legacies of colonialism, epistemicide, and cultural erasure across educational systems in the Mediterranean region, emphasising the need for intercultural and emotionally intelligent leadership grounded in care, listening, and epistemic justice. Through illustrative examples from Portugal, Spain, Algeria, and Tunisia, it highlights educational practices that resist technocratic models and nurture inclusive, community-rooted learning environments. Incorporating insights from Islamic educational thought, Maghrebi feminism, and the Epistemologies of the South, the text advocates pedagogical approaches that embrace plural rationalities, cultural reterritorialisation, and a shared ethics of dignity. The structure follows four thematic axes: ethical leadership in peripheral schools; pedagogical engagement with marginalised youth; inclusive, affective educational practices; and the construction of interregional educational alliances. The conclusion calls for a new educational pact based on epistemic co-authorship and cognitive justice. Education is understood not merely as instruction, but as an insurgent space for reimagining futures, healing historical wounds, and cultivating radical hope.